Acoustic signals and behaviour of Ovalipes trimaculatus in the context of reproduction - G Buscaino (Inter-Research, 2015)
This study focused on the acoustic behaviour of the paddle crab Ovalipes trimaculatus (De Haan, 1833) in relation to its reproductive status and behaviour. Paired males and females (demonstrating pre-copulatory behaviour) as well as solitary animals were collected a few hundred metres from the coast of Puerto Madryn (Patagonia, Argentina) and kept in indoor tanks. Synchronized acoustic and video monitoring systems were used to record the acoustic signals and other behaviours of single and grouped specimens in an experimental tank. Acoustic data were analysed to characterize crab sounds (duration, pulse number and pulse rate, 1st and 2nd peaks in frequency, amplitude of the frequency peaks and bandwidth) and were counted as behavioural events. Video data were analysed to count behavioural events (i.e. agonistic fight, chela spread) and determine status (locomotor indices, inter-crab distance). O. trimaculatus produced wide frequency band multi-pulse signals with significant differences between males and females: males showed a lower 1st peak in frequency, with a higher amplitude and a higher bandwidth. The sound emission rate was significantly higher in grouped animals than in single individuals. The sound emissions were not accidental events correlated with locomotor activities. In the trials involving pre-copulatory females, the total number of sounds was significantly higher compared to the trials with non-copulatory (control) females, and the sounds were not correlated with the agonistic events between males. Our data indicate that in O. trimaculatus sound emissions play a role in intraspecific communication related to sexual attraction.